Shiloh - Naylor, Phyllis Reynolds (New York : Atheneum ; Toronto : Collier Macmillan Canada ; New York : Maxwell Macmillan International Pub. Group, 1991)
When he finds a lost beagle in the hills behind his West Virginia home, Marty tries to hide it from his family and the dog's real owner, a mean-spirited man known to shoot deer out of season and to mistreat his dogs.
Keywords: Dogs -- Fiction; Animals -- Treatment -- Fiction; West Virginia -- Fiction